Knowledge and Practices on Neonatal Care among Selected Mothers Attending Dhaka Shishu Hospital - Begum, Housne Ara; Khan, Mohammad Faizul Haque (Ibrahim Medical College Journal, 2010)
This study was conducted in Dhaka Shishu Hospital from December 2007 to February 2008 and was based on primary data on knowledge and practice of 400 mothers of neonates attending the hospital. More than 50% of the mothers had appropriate knowledge on feeding, hand washing, care of eye and umbilicus and they were practicing as well. Less than 50% of the mothers had an appropriate knowledge on raising neonates, shaving hair, bathing, vaccination, oil massaging and their practice rates also did commensurate with their knowledge level. It may be concluded that half of the interviewed mothers had an inadequate knowledge and adopted inappropriate practices in the care of their neonates. Strong steps should be taken to improve the level of knowledge and change attitudes for providing healthy practices of mothers in the care of their children. Ibrahim Med. Coll. J. 2009; 3(2): 59-62 DOI: 10.3329/imcj.v3i2.4218